Mass Balance Analysis of Carbon Black Production from Waste Polyethylene Terephthalate (PET) - Apridio Faiz An Nabil; Irsya Emilia Putri; Wiliandi Saputro; Erwan Adi Saputro (Future Science, 2022)
Carbon black is an important member of the family of industrial carbons. Carbon black is defined as a black substance in the form of a powder or granule. One form of innovation in the manufacture of carbon black is by using Polyethylene Terephthalate (PET) plastic waste as an effort to be able to help overcome the problem of waste accumulation in Indonesia. In addition, it can also be used as an effort to meet the needs of industrial raw materials and the problem of dependence on imports of carbon black raw materials in Indonesia. This study aims to observe the manufacture of carbon black from Polyethylene Terephthalate (PET) plastic waste with a mass balance. The manufacture of carbon black consists of a plastic waste collection process, washing, drying, size reduction, carbonization process, reduction and uniformity of carbon black size. The process of making carbon black uses 1.5 kg of plastic waste Polyethylene Terephthalate (PET) as the starting material and produces 551.7 so we get the percent of yield black carbon production is 36.78%.